Becoming a Thinking Thinker: Metacognition, Self-Reflection, and Classroom Practice - Desautel, Daric (Teachers College record (1970), 2009)
Background/Context: Metacognition has been a subject of study for cognitive theorists, behaviorists, educators, and others. The term metacognition has traditionally and simply been defined as "thinking about thinking," yet it describes a complex process that can result in a nuanced understanding of oneself as a thinker and a learner. Metacognition (as a process) and metacognitive knowledge (as a product) are seen as important components of cognitive development and signs of intellectual maturity. The development of metacognitive knowledge is not, however, reserved for adult learners. Robust metacognitive knowledge can help young students consciously apply learning strategies, develop effective work habits, and assess their own performance. Objective: The purpose of this study was to explore what practices lead to successful self-reflection and promote metacognitive development in young learners. The author believes that elementary students who are aware of their tasks and have knowledge of themselves as learners will more effectively apply learning strategies, develop effective work habits, and generally enjoy a richer learning experience. In the interest of best classroom practices, the author has selected activities and routines that complement the existing curriculum and instructional program. Setting: This study was conducted in an urban elementary school. Participants: This study was conducted by a classroom teacher with his second-grade students. These students include English language learners of a range of ethnicities, students who receive special education services, and general education students. Research Design: This action research study was designed as a qualitative case study. After assessing student metacognitive knowledge with a survey of reading strategies, the author began a course of instruction in skills and habits that he believed might promote self-reflection and metacognition. These skills and habits included directed goal-setting, the use of language prompts to articulate mental events, posttask written self-reflections, and posttask oral conversations. Data collected following this instruction consisted of observations of student interactions, written records of students' conferences along with the academic goals they set on a weekly basis, and the written products of reflective journal writing and posttask self-reflections.